2005
DOI: 10.1063/1.2010605
|View full text |Cite
|
Sign up to set email alerts
|

Direct studies of domain switching dynamics in thin film ferroelectric capacitors

Abstract: Kingon, A. I.; Nemanich, R. J.; and Cross, J. S., "Direct studies of domain switching dynamics in thin film ferroelectric capacitors" (2005). Alexei Gruverman Publications. 16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
182
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(193 citation statements)
references
References 24 publications
11
182
0
Order By: Relevance
“…Subsequent examination of domain structures produced by the switching event provides the information on switching mechanism. Recent studies by Gruverman et al have shown that domain nucleation in ferroelectric capacitors is always initiated at the same defect regions; 29 similarly, the grain boundaries were shown to play an important role in domain wall pinning. 30 Paruch and coworkers have used local studies of domain growth kinetics 31 and domain wall morphology 32 to establish the origins of disorder in ferroelectric materials.…”
Section: Current Results On Nanoscale Polarization Dynamicsmentioning
confidence: 99%
“…Subsequent examination of domain structures produced by the switching event provides the information on switching mechanism. Recent studies by Gruverman et al have shown that domain nucleation in ferroelectric capacitors is always initiated at the same defect regions; 29 similarly, the grain boundaries were shown to play an important role in domain wall pinning. 30 Paruch and coworkers have used local studies of domain growth kinetics 31 and domain wall morphology 32 to establish the origins of disorder in ferroelectric materials.…”
Section: Current Results On Nanoscale Polarization Dynamicsmentioning
confidence: 99%
“…Here we report the direct observation of a doughnutshape domain pattern appearing during polarization reversal in micrometer-sized ferroelectric capacitors [13]. The switching behavior of the out-of-plane polarization component P z showing nucleation and wall propagation along the electrode edge, as well as evolution of the in-plane polarization components P x and P y , were simulated using the Landau-Lifshitz-Gilbert (LLG) equations.…”
mentioning
confidence: 99%
“…The field was then applied for a longer time interval and the imaging PFM procedure repeated. Because domain nucleation is nearly 100% inhomogeneous in PZT, occurring at the same defect sites, it was then possible to superimpose the collection of images obtained for differ- ent pulse durations to form a slow-motion video of nucleation and domain wall motion during polarization reversal [13]. Domain imaging has been performed through the top electrode by applying an oscillating bias of 0.6 V (peakto-peak) at 10 kHz.…”
mentioning
confidence: 99%
“…20 Recent PFM experiments revealed the ability to directly observe domains in multiferroics and to control their switching behavior using electric fields. [16][17][18][19][20] Switching studies in PFM have focused mainly on imaging before and after switching and the details of the ferroelectric domain evolution during application of the field remains to be understood. This represents one of the limitations of PFM and other scanning-probe-based techniques in providing information on switching in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] One of the most notable techniques is piezoresponse force microscopy (PFM), which has given great insight into the nature of polarization switching in ferroelectric materials, including studies of nucleation at free surfaces 18 and in capacitor structures, 19 nucleation mechanisms, and domain wall dynamics. 20 Recent PFM experiments revealed the ability to directly observe domains in multiferroics and to control their switching behavior using electric fields.…”
Section: Introductionmentioning
confidence: 99%